Hepatitis B virus DNA level Among the Seropositive Afghan Immigrants, Southern Iran - Behzadi, Mohammad Amin (Kowsar, 2014)
BACKGROUND: Diagnosis and control programs for infectious diseases among immigrants are the most important aspects of epidemiological studies for both origin and destination countries. Data about hepatitis B virus (HBV) infection among the Afghan immigrants in Iran is limited. OBJECTIVES: To the best of HBV treatment and prevention in Afghan immigrants in Iran, the present study was conducted to determine the virus DNA level, and the frequency of respective hepatitis B risk factors among the respective seropositive patients in Fars province, southern Iran. PATIENTS AND METHODS: A total of 64 HBsAg positive Afghan immigrants including 47 (73.4%) men and 17 (26.6%) women, with ages ranging between 15 and 74 years (mean ± standard deviation: 37.69 ± 15.02 years) participated in this study. From those, whole blood sample were collected and DNAs were extracted from the sera and analyzed by TaqMan real-time PCR assay with a set of primers and probe amplified core protein region of HBV genome. RESULTS: HBV DNA was detected in a total of 51/64 (79.7 %) serum samples; 37 (72.5%) male and 14 (27.5%) female. The copy number of HBV DNA ranged from 5 × 10(2) to 8.49 × 10(8) copies/mL in the serum samples; median 3.8 × 10(4) copies/mL. Demographic data and risk factors were also evaluated. The comparison of viral loads between the age groups and sex indicated no significant correlation (P > 0.05). However, the serum HBV DNA level significantly decreased in the treated patient group (P = 0.03). There was no significant difference in medicine usage between the two sexes in the study population (P > 0.05). CONCLUSIONS: Considering the results, determining the HBV DNA load and evaluation of treatment response can help to reduce the costs of diagnosis and treatment procedures in such patients, as well as, decreasing the risk of HBV transmission in immigrant Afghan population. Moreover, HBV screening strategies in country border entrances among immigrant should be performed. Moreover, free vaccination and treatment programs, and improving the level of HBV knowledge among Afghan immigrants in Iran is highly recommended.